On the Geometry of Ghosts. Issue 2 (October 2016) - Canarutto, Daniel
Abstract : An inspection of the precise geometric constructions underlying fundamental notions in quantum gauge field theories sheds light on various aspects which tend to be obscured in the usual formalisms. Revising the notions of mutually conjugated "internal" bundles we propose a general rule for the constructions of free quantum fields and their conjugates, naturally yielding the needed fundamental properties with regard to contractions, super-commutators, field momentum and Hamiltonian, and other quantities. This scheme applies to fields of all types; in particular we examine consequences in relation to ghosts and anti-ghosts. Finally in the context of observer-independent Frölicher-smooth quantum bundles we show how the antifield sectors naturally arise, and examine the precise relation among these and the BRST symmetry of a gauge field theory.